Electrochemical determination of disulfoton using a molecularly imprinted poly-phenol polymer. (1st February 2019) - Qader, Bakhtiyar; Baron, Mark; Hussain, Issam; Sevilla, J.M.; Johnson, Robert P.; Gonzalez-Rodriguez, Jose
Abstract: A simple, rapid and sensitive electrochemical method using a molecularly imprinted poly-phenol polymer for the analysis of disulfoton in model and real samples is demonstrated. A computational approach to molecularly imprinted polymer design and screening is followed using density functional (B3LYP) and Semi-Empirical Parameterized Model number 3 (PM3) models. The selected phenol monomer is electrochemically polymerized by cyclic voltammetry at a glassy carbon working electrode in the presence of a disulfoton template. The subsequent molecularly imprinted polymer sensor exhibits an oxidation peak at 1.13 V vs. Ag/AgCl in cyclic voltammetry with excellent linearity (r 2 = 0.9985) over the range 1–30 μM. The limit of detection for the DSN-MIP is 0.183 μM, compared to a limit of detection of 1.64 μM with cyclic voltammetry for the bare glassy carbon electrode. Intra- and inter-day assay precisions, expressed as relative standard deviation, are both found to be less than 7% overall. The developed molecularly imprinted polymer sensor is utilized to determine disulfoton in both spiked synthetic human plasma and human urine samples with recoveries ranging from 85.2% to 101.1%. The developed methods can be applied for measuring this toxicant in a real sample.